2019
DOI: 10.3390/su11164378
|View full text |Cite
|
Sign up to set email alerts
|

Validation of UWG and ENVI-Met Models in an Abu Dhabi District, Based on Site Measurements

Abstract: The city of Abu Dhabi is growing every year in population, urban extent and energy demand. This research focuses on the application of two simulation programs to estimate changes in urban climate associated with continued development in Abu Dhabi: The Urban Weather Generator (UWG) and ENVI-met. Simulation with these two software packages are validated with the site data measured in downtown Abu Dhabi. A comparison analysis (in the different seasons) between the rural data, the simulation output, and the site m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(17 citation statements)
references
References 24 publications
(49 reference statements)
1
16
0
Order By: Relevance
“…These findings are coincident with investigations of Bande et al (2019) in Abu Dhabi, which showed that the UWG model tends to overestimate the canyon temperature during the summer and has a more realistic estimation in the winter season. Anyway, EN-VI-met has better estimations of temperatures during the summer season compared to the UWG.…”
Section: Discussionsupporting
confidence: 89%
“…These findings are coincident with investigations of Bande et al (2019) in Abu Dhabi, which showed that the UWG model tends to overestimate the canyon temperature during the summer and has a more realistic estimation in the winter season. Anyway, EN-VI-met has better estimations of temperatures during the summer season compared to the UWG.…”
Section: Discussionsupporting
confidence: 89%
“…The strategies are based on a combination of trees and shading structures applied in the walking paths or courtyards of the neighborhoods. The trees studied (applied in the simulation models) are local trees, and the shading devices refer to a structure analyzed in a previous study done for the OTC study of downtown Abu Dhabi [21]. The second step is taking site measurements for the boundary conditions of the CFD (Computational Fluid Dynamic) software used in this study.…”
Section: Methodsmentioning
confidence: 99%
“…The main factor that changes in these two districts is the relative humidity. Table 2 shows the different scenarios considered in this study [21]. The difference between the scenarios is mainly in the percentage of trees and shading devices used in order to understand the optimal proportion for an optimal PMV value at the specific season/day considered in this study.…”
Section: District Selection/scenarios Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Mega cities like Dubai and Abu Dhabi have green standards in the urban planning sector and these are being extended to medium sized cities like Al Ain as well [15]. Implementation of such standards in urban planning or retrofitting existing infrastructure and buildings requires careful modelling of the local micro-climatic patterns [16]. In this study, the microclimate variation and UHI were assessed for Al Ain city using the LCZ mapping approach, while ENVImet was used to model each of the LCZ considered in the study.…”
Section: Introductionmentioning
confidence: 99%